Ensuring Defense Counsel Competence at International Criminal Tribunals - Starr, Sonja B. (2009)
This article addresses the problem of incompetent representation by defense counsel in international criminal tribunals. According to the author, the ineffectiveness of a particular attorney may be attributable to a number offactors, including a lack of experience with international criminal law, unfamiliarity with the procedures of international criminal tribunals, and the simple failure to be fluent in the languages used by the court. Starr explains that the problem of incompetence persists because of obstacles to the recruitment, retention, and appointment of proficient defense lawyers, as well as the lack of administrative or judicial oversight concerning competence. The author points out the shortcomings of solutions that have already been suggested by scholars and advocates, such as establishing associations of counsel or creating an Office of the Defender within the tribunal. Finally, Starr sets forth a new method by which the International Criminal Court can hopefully avoid the incompetence problem that has plagued its predecessors. The author's proposed solution incorporates expanded recruiting practices, intensive training programs, and a more selective appointment process